2021
DOI: 10.3390/antiox10060953
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Vitamin C and Cysteine Deficiencies Program Adult Hepatic Glutathione and Specific Activities of Glucokinase, Phosphofructokinase, and Acetyl-CoA Carboxylase in Guinea Pigs’ Livers

Abstract: Premature neonates are submitted to an early-life oxidative stress from parenteral nutrition, which is vitamin C (VC) deficient and induces low endogenous levels of glutathione. The oxidative stress caused by these deficiencies may permanently affect liver glycolysis and lipogenesis. This study evaluates the short- and long-term effects of neonatal VC and cysteine deficient diets on redox and energy metabolism. Three-day-old Hartley guinea pigs from both sexes were given a regular or a deficient diet (VC, cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…During sacrifice, lungs and liver were collected and quickly frozen at −80 • C and kept at this temperature until biochemical determinations. The study experimental design, including diet composition, has been published before [7].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During sacrifice, lungs and liver were collected and quickly frozen at −80 • C and kept at this temperature until biochemical determinations. The study experimental design, including diet composition, has been published before [7].…”
Section: Methodsmentioning
confidence: 99%
“…Ascorbate was resolved in a 50 µM/45 cm silica capillary, 25 • C, 30 kV in an Agilent 7100 Capillary Electrophoresis System (Agilent Technologies, Mississauga, ON, Canada). Separation was performed in boric acid 200 mM and acetonitrile 20% v/v buffer, pH 9.6, and detection of ascorbate was performed by absorbance at 268 nm [7,21].…”
Section: Gsh Gssg and Ascorbatementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the ACC gene in medicine have found that cancer cells can reprogram the lipid metabolism during malignant progression, and ACC plays a key role in regulating the growth and differentiation of leukemic initiation cells. In addition, adenosine monophosphate-activated protein kinase (AMPK) can inhibit ACC, reduce the consumption of Nicotinamide Adenine Dinucleotide Phosphate (NADPH) in fatty acid synthesis, and generate homeostasis [22][23][24]. At present, there are few studies on the changes in ACC gene expression in aquatic animals under cold stress.…”
Section: Introductionmentioning
confidence: 99%